Example #1
0
        /// <summary>
        /// Expand a power expression.
        /// </summary>
        /// <param name="f"></param>
        /// <param name="x"></param>
        /// <returns></returns>
        private static Expression ExpandPower(Power f, Expression x)
        {
            // Get integral exponent of f.
            int n = Power.IntegralExponentOf(f);

            // If this is an an integral constant negative exponent, attempt to use partial fractions.
            if (n < 0 && !ReferenceEquals(x, null))
            {
                Expression b = f.Left.Factor(x);
                if (n != -1)
                {
                    b = Power.New(b, Math.Abs(n));
                }
                return(ExpandPartialFractions(1, b, x));
            }

            // If f is an add expression, expand it as if it were multiplication.
            if (n > 1 && f.Left is Sum)
            {
                Expression e = f.Left;
                for (int i = 1; i < n; ++i)
                {
                    e = Distribute(f.Left, e);
                }
                return(e);
            }

            return(f);
        }
Example #2
0
        protected override Expression VisitPower(Power P)
        {
            Expression L = Visit(P.Left);
            Expression R = Visit(P.Right);

            if (R.IsInteger())
            {
                // Transform (x*y)^z => x^z*y^z if z is an integer.
                Product M = L as Product;
                if (!ReferenceEquals(M, null))
                {
                    return(Visit(Product.New(M.Terms.Select(i => Power.New(i, R)))));
                }
            }

            // Transform (x^y)^z => x^(y*z) if z is an integer.
            Power LP = L as Power;

            if (!ReferenceEquals(LP, null))
            {
                L = LP.Left;
                R = Visit(Product.New(P.Right, LP.Right));
            }

            // Handle identities.
            Real?LR = AsReal(L);

            if (EqualsZero(LR))
            {
                return(0);
            }
            if (EqualsOne(LR))
            {
                return(1);
            }

            Real?RR = AsReal(R);

            if (EqualsZero(RR))
            {
                return(1);
            }
            if (EqualsOne(RR))
            {
                return(L);
            }

            // Evaluate result.
            if (LR != null && RR != null)
            {
                return(Constant.New(LR.Value ^ RR.Value));
            }
            else
            {
                return(Power.New(L, R));
            }
        }
Example #3
0
        /// <summary>
        /// Distribute products across sums.
        /// </summary>
        /// <param name="f"></param>
        /// <param name="x"></param>
        /// <returns></returns>
        public static Expression Factor(this Expression f, Expression x)
        {
            // If f is a product, just factor its terms.
            if (f is Product)
            {
                return(Product.New(((Product)f).Terms.Select(i => i.Factor(x))));
            }

            // If if is l^r, factor l and distribute r.
            if (f is Power)
            {
                Expression l = ((Power)f).Left.Factor(x);
                Expression r = ((Power)f).Right;
                return(Product.New(Product.TermsOf(l).Select(i => Power.New(i, r))));
            }

            // If f is a polynomial of x, use polynomial factoring methods.
            if (f is Polynomial && (((Polynomial)f).Variable.Equals(x) || ReferenceEquals(x, null)))
            {
                return(((Polynomial)f).Factor());
            }

            // Try interpreting f as a polynomial of x.
            if (!ReferenceEquals(x, null))
            {
                // If f is a polynomial of x, factor it.
                try
                {
                    return(Polynomial.New(f, x).Factor());
                }
                catch (Exception) { }
            }

            // Just factor out common sub-expressions.
            if (f is Sum)
            {
                Sum s = (Sum)f;

                IEnumerable <Expression> terms = s.Terms.Select(i => i.Factor()).Buffer();

                // All of the distinct factors.
                IEnumerable <Expression> factors = terms.SelectMany(i => FactorsOf(i).Except(1, -1)).Distinct();
                // Choose the most common factor to use.
                Expression factor = factors.ArgMax(i => terms.Count(j => FactorsOf(j).Contains(i)));
                // Find the terms that contain the factor.
                IEnumerable <Expression> contains = terms.Where(i => FactorsOf(i).Contains(factor)).Buffer();
                // If more than one term contains the factor, pull it out and factor the resulting expression (again).
                if (contains.Count() > 1)
                {
                    return(Sum.New(
                               Product.New(factor, Sum.New(contains.Select(i => Binary.Divide(i, factor))).Evaluate()),
                               Sum.New(terms.Except(contains, Expression.RefComparer))).Factor(null));
                }
            }

            return(f);
        }
Example #4
0
        /// <summary>
        /// Distribute products across sums.
        /// </summary>
        /// <param name="f"></param>
        /// <param name="x"></param>
        /// <returns></returns>
        public static Expression Factor(this Expression f, Expression x)
        {
            // If f is a product, just factor its terms.
            if (f is Product product)
            {
                return(Product.New(product.Terms.Select(i => i.Factor(x))));
            }

            // If if is l^r, factor l and distribute r.
            if (f is Power power)
            {
                Expression l = power.Left.Factor(x);
                Expression r = power.Right;
                return(Product.New(Product.TermsOf(l).Select(i => Power.New(i, r))));
            }

            // If f is a polynomial of x, use polynomial factoring methods.
            if (f is Polynomial p && (p.Variable.Equals(x) || (x is null)))
            {
                return(p.Factor());
            }

            // Try interpreting f as a polynomial of x.
            if (!(x is null))
            {
                // If f is a polynomial of x, factor it.
                try
                {
                    return(Polynomial.New(f, x).Factor());
                }
                catch (Exception) { }
            }

            // Just factor out common sub-expressions.
            if (f is Sum s)
            {
                // Make a list of each terms' products.
                List <List <Expression> > terms = s.Terms.Select(i => FactorsOf(i).ToList()).ToList();

                // All of the distinct factors.
                IEnumerable <Expression> factors = terms.SelectMany(i => i.Except(1, -1)).Distinct();
                // Choose the most common factor to factor.
                Expression factor = factors.ArgMax(i => terms.Count(j => j.Contains(i)));
                // Find the terms that contain the factor.
                List <List <Expression> > contains = terms.Where(i => i.Contains(factor)).ToList();
                // If more than one term contains the factor, pull it out and factor the resulting expressions (again).
                if (contains.Count() > 1)
                {
                    Expression factored     = Sum.New(contains.Select(i => Product.New(i.Except(factor))));
                    Expression not_factored = Sum.New(terms.Except(contains).Select(i => Product.New(i)));
                    return(Sum.New(Product.New(factor, factored), not_factored).Factor(null));
                }
            }
            return(f);
        }
Example #5
0
        // Expand N(x)/D(x) using partial fractions.
        private static Expression ExpandPartialFractions(Expression N, Expression D, Expression x)
        {
            List <Expression> terms    = new List <Expression>();
            List <Variable>   unknowns = new List <Variable>();
            List <Expression> basis    = new List <Expression>();

            foreach (Expression i in Product.TermsOf(D))
            {
                // Get the multiplicity of this basis term.
                Expression e = i;
                int        n = Power.IntegralExponentOf(e);
                if (n != 1)
                {
                    e = ((Power)i).Left;
                }

                // Convert to a polynomial.
                Polynomial Pi = Polynomial.New(e, x);

                // Add new terms for each multiplicity n.
                for (int j = 1; j <= n; ++j)
                {
                    // Expression for the unknown numerator of this term.
                    Expression unknown = 0;
                    for (int k = 0; k < Pi.Degree; ++k)
                    {
                        Variable Ai = Variable.New("_A" + unknowns.Count.ToString());
                        unknown += Ai * (x ^ k);
                        unknowns.Add(Ai);
                    }

                    terms.Add(Product.New(unknown, Power.New(e, -j)));
                }
                basis.Add(i);
            }

            // Equate the original expression with the decomposed expressions.
            D = Sum.New(terms.Select(j => (Expression)(D * j))).Expand();
            Polynomial l = Polynomial.New(N, x);
            Polynomial r = Polynomial.New(D, x);

            // Equate terms of equal degree and solve for the unknowns.
            int          degree = Math.Max(l.Degree, r.Degree);
            List <Equal> eqs    = new List <Equal>(degree + 1);

            for (int i = 0; i <= degree; ++i)
            {
                eqs.Add(Equal.New(l[i], r[i]));
            }
            List <Arrow> A = eqs.Solve(unknowns);

            // Substitute the now knowns.
            return(Sum.New(terms.Select(i => i.Evaluate(A))));
        }
Example #6
0
        // Combine like terms and multiply constants.
        protected override Expression VisitProduct(Product M)
        {
            // Map terms to exponents.
            DefaultDictionary <Expression, Real> terms = new DefaultDictionary <Expression, Real>(0);

            // Accumulate constants and sum exponent of each term.
            Real C = 1;

            foreach (Expression i in M.Terms.SelectMany(i => Product.TermsOf(Visit(i))))
            {
                if (i is Constant)
                {
                    Real Ci = (Real)i;
                    // Early exit if 0.
                    if (Ci.EqualsZero())
                    {
                        return(0);
                    }
                    C *= Ci;
                }
                else
                {
                    Power Pi = i as Power;
                    if (!ReferenceEquals(Pi, null) && Pi.Right is Constant)
                    {
                        terms[Pi.Left] += (Real)Pi.Right;
                    }
                    else
                    {
                        terms[i] += 1;
                    }
                }
            }

            // Build a new expression with the accumulated terms.
            if (!C.EqualsOne())
            {
                // Find a sum term that has a constant term to distribute into.
                KeyValuePair <Expression, Real> A = terms.FirstOrDefault(i => Real.Abs(i.Value).EqualsOne() && i.Key is Sum);
                if (!ReferenceEquals(A.Key, null))
                {
                    terms.Remove(A.Key);
                    terms[ExpandExtension.Distribute(C ^ A.Value, A.Key)] += A.Value;
                }
                else
                {
                    terms.Add(C, 1);
                }
            }
            return(Product.New(terms
                               .Where(i => !i.Value.EqualsZero())
                               .Select(i => !i.Value.EqualsOne() ? Power.New(i.Key, Constant.New(i.Value)) : i.Key)));
        }
        // V((A*x)^n) = A^(1/n)*V(x^n)
        protected override Expression VisitPower(Power P)
        {
            if (!IsConstant(P.Right))
            {
                return(base.VisitPower(P));
            }

            Expression L = P.Left.Factor();

            IEnumerable <Expression> A = Product.TermsOf(L).Where(i => IsConstant(i));

            if (A.Any())
            {
                return(Product.New(Power.New(Product.New(A), 1 / P.Right), Visit(Product.New(Product.TermsOf(L).Where(i => !IsConstant(i))))));
            }
            return(base.VisitPower(P));
        }
Example #8
0
        protected override Expression VisitPower(Power P)
        {
            Expression f = P.Left;
            Expression g = P.Right;

            if (g.DependsOn(x))
            {
                // f(x)^g(x)
                return(Product.New(P,
                                   Sum.New(
                                       Product.New(Visit(f), Binary.Divide(g, f)),
                                       Product.New(Visit(g), Call.Ln(f)))).Evaluate());
            }
            else
            {
                // f(x)^g
                return(Product.New(
                           g,
                           Power.New(f, Binary.Subtract(g, 1)),
                           Visit(f)).Evaluate());
            }
        }
Example #9
0
        /// <summary>
        /// Construct a polynomial of x from f(x).
        /// </summary>
        /// <param name="f"></param>
        /// <param name="x"></param>
        /// <returns></returns>
        public static Polynomial New(Expression f, Expression x)
        {
            // Match each term to A*x^N where A is constant with respect to x, and N is an integer.
            Variable   A           = PatternVariable.New("A", i => !i.DependsOn(x));
            Variable   N           = PatternVariable.New("N", i => i.IsInteger());
            Expression TermPattern = Product.New(A, Power.New(x, N));

            DefaultDictionary <int, Expression> P = new DefaultDictionary <int, Expression>(0);

            foreach (Expression i in Sum.TermsOf(f))
            {
                MatchContext Matched = TermPattern.Matches(i, Arrow.New(x, x));
                if (Matched == null)
                {
                    throw new ArgumentException("f is not a polynomial of x.");
                }

                int n = (int)Matched[N];
                P[n] += Matched[A];
            }

            return(new Polynomial(P, x));
        }
Example #10
0
 public static LazyExpression operator /(Expression L, Expression R)
 {
     return(new LazyExpression(Product.New(L, Power.New(R, -1))));
 }
 public static LazyExpression operator /(LazyExpression L, LazyExpression R)
 {
     return(new LazyExpression(Product.New(L.value, Power.New(R.value, -1))));
 }